ANALISIS PEMANFAATAN MEDIA PEMBELAJARAAN SOSIOLOGI BERBANTUAN INTERNET OLEH GURU PADA KELAS XI IPS MAN 2 PONTIANAK - Handriani, Novi; Rustiyarso, Rustiyarso; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe general problem in this research was  The Use of Internet-assisted Sociology Teaching Media by Teachers in Class XI IPS MAN 2 Pontianak. This research was done by descriptive research method with the qualitative research form. The research technique used documentation techniques with data collection tools in the form of interview and observation guidelines. From the results of observations, the researcher can be concluded that the utilization of internet assisted learning media by teachers. Teacher takes advantage of various websites on the internet such as websites.Web-based learning is one of the learning activities that utilize the media sites (websites) that can be accessed through the internet network.  In the process of studying teachers choose web-based learning that was most appropriate and in accordance with the objectives to be achieved.to begin the processof learning should choose the type of web-based  learning where the most appropriate,first determine the domain of learning that present the most goals,they are cognitive,psychomotor, or effective.  Internet media used by sociology teacher at MAN 2 Pontianak uses website to help easer in the learning process by using the internet.  Keywords: Utilization of learning media,internet help.